Speech text of The 2nd International Conference on Islam and Global Issues 2024 (ICIGI2024) / Prof. Datuk Dr. Shahrin Sahib @ Sahibuddin - Sahib @ Sahibuddin, Shahrin (2024)
1. Alhamdulillah, we give thanks to Allah SWT for His grace and blessings, which have allowed us to assemble on this auspicious day for the International Conference on Islam and Global Issues (ICIGI) 2024. 2. I am pleased to welcome everyone joining us today. Thank you for your invaluable contributions to the success of this momentous event. I am grateful for your active participation and unwavering commitment to the spirit of ICIGI2024.